2007
DOI: 10.1007/s10342-006-0153-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of forest management on trace gas exchange at the pedosphere–atmosphere interface in beech (Fagus sylvatica L.) forests stocking on calcareous soils

Abstract: The effect of forest management (thinning) on in situ carbon dioxide (CO 2 ), methane (CH 4 ) and nitrous oxide (N 2 O) trace gas exchange between soil and atmosphere was studied in three consecutive years at three beech forest sites, which differ in aspect [southwest (SW), northeast (NE), northwest (NW)]. At all sites adjacent thinning plots (''T'') and untreated control plots (''C'') were established. Measurements at the SW and NE sites covered the years 4-6 after thinning while at the NW site measurements c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 52 publications
5
49
1
Order By: Relevance
“…This may be ascribed to the fact that these values were determined about three years after logging. A significant increase in soil water content as a result of the reduction of evapotranspiration and hence water uptake by trees has been documented not only in clear-cutting studies (Castro et al, 2000;Zerva and Mencuccini, 2005), but also in a study on forest selective cutting (Dannenmann et al, 2007), which is consistent with our findings.…”
Section: Effect Of Forest Management On Environmental Factorssupporting
confidence: 92%
See 3 more Smart Citations
“…This may be ascribed to the fact that these values were determined about three years after logging. A significant increase in soil water content as a result of the reduction of evapotranspiration and hence water uptake by trees has been documented not only in clear-cutting studies (Castro et al, 2000;Zerva and Mencuccini, 2005), but also in a study on forest selective cutting (Dannenmann et al, 2007), which is consistent with our findings.…”
Section: Effect Of Forest Management On Environmental Factorssupporting
confidence: 92%
“…Published studies on the effect of forest selective cutting on soil CH 4 flux were rather scarce, especially for long-term data, and sometimes contradictory. Dannenmann et al (2007) reported a distinct decrease in soil CH 4 uptake in the first year after thinning of a beech forest, but no significant changes of CH 4 fluxes at another nearby site 4e6 years after selective cutting. One laboratory study done by Bradford et al (2000) showed a significantly higher CH 4 uptake in soil cores from a selectively logged oak forest site than that from an undisturbed site.…”
Section: Effect Of Selective Cutting On Soil Ch 4 Fluxesmentioning
confidence: 89%
See 2 more Smart Citations
“…Abetz & Ohnenus 1999;Tarp et al 2000;Bastien et al 2005;Boncina et al 2007;Hein et al 2007;Štefančík 2013a) but also in the frame of other forest services. Thinning in beech stands is important for the cycles of carbon (Borys et al 2013) and nitrogen (Nahm et al 2006;Dannenmann et al 2007a), and also climate (Le Goff & Ottorini 1993;Cescatti & Piutti 1998;Barna 2000Barna , 2001Lemoine et al 2002;Dannenmann et al 2007b;Štefančík 2008). The positive effect of thinning on beech stands (higher increment, longer growth period compared to unthinned stands) under the climate change was confirmed by van der Maaten (2013).…”
Section: Introductionmentioning
confidence: 99%